L’Empathie comme base de réflexion sur l’identité des marqueurs HAVE et WANT - Philippe Muller (Anglophonia)
In the wake of previous papers from French linguists who used the word “empathy” to describe the operators AVOIR and HAVE, it is suggested that this notion should be conceived of as an interpretation process connected with the localization operation as defined in enunciative theories. It is proposed that this process hinges on the speaker and co-speaker assessing the necessity of establishing a relation between a located term and a locator through an operator. Such a relation must bring about a (re)qualification of the locator capable of justifying its status as the central topic in the situation being described. This state of affair creates a whole-part relationship between the redefined locator and the situation itself whereby the latter undergoes a differentiation process. It is then suggested that empathy is what lets the HAVE-predication sometimes be analysed as a subjectified existential phrase. It is also what really underlies the recent claims about WANT concerning the development of volition out of a notion of deficit. This process seems to remain synchronically relevant for that marker and complements the concept of “intentionality” that is used in Culioli’s speaker-centred approach and which could serve as a basis for distinguishing between WANT and NEED. Finally, it is shown that the empathy associated with WANT can be advantageously utilised in discourse in a specific narrative pattern, that of the “circle story”.